Development and Applications of Differential Scanning Calorimetric Methods for Physical and Chemical Analysis of Palm Oil - H. M. Salim, Tri Haryati (1999)
Fractionation is accomplished by exploiting different crystallisation point of triglyceride (TG). This theoretical basis exposes the importance of thermal behaviour of the palm oil on the success of the fractionation process as well as the use of differential scanning calorimeter (DSC) for analysing some palm oil parameters. In this study, new methods to determine melting point (MP), cloud point (CP), iodine value (IV), and the composition of TG groups of palm oil were developed. The methods were then applied for monitoring chemical transesterification. The appropriate running conditions of DSC for analysing palm oil were heating and cooling rate of 5°C/min, holding time of 5 minutes and sample weight of 2.3 - 18.4 mg. Regression models to calculate MP, CP, and IV of standard methods were developed. For MP, the offset temperature from the heating thermogram was used to develop the model, while for CP and IV, the models used onset temperature and energy, respectively, from cooling thermogram. Using similar theoretical background as in IV, models to calculate trisaturated and triunsaturated TG concentration were developed. Regression models were developed to calculate trisaturated TG using energy in cooling thermogram and triunsaturated TG using energy either in cooling or heating thermograms. The study have shown that all DSC methods developed were more consistent than the standard AOCS methods. Redistribution of the fatty acids was achieved through chemical transesterification. Using response surface methodology, trisaturated TG obtained from high performance liquid chromatography (HPLC) increased 2.1 times and triunsaturated TG increased 1.88 times from the original. Using DSC, the increase was 2.14 times for trisaturated and 1.92 times for triunsaturated.